INTENSITY OF THE HEAVY METALS ACCUMULATION BY SUNFLOWER SEEDS AND MEAL - Hutsol , Г.; Mazur , О. (Bulletin of Lviv National Environmental University. Series Agronomy, 2023)
The current situation shows that sunflower is still one of the most profitable products at the domestic market, which is fully saturated by its own production. The fertility of soil in Vinnytsia region provide favorable conditons for frowing sunflower, and its wide range of use contributes to a gradual increase in the area under sunflower cultivation. The growth of sunflower acreage in Ukraine is accompanied by an increase in the application rates of mineral fertilizers and pesticides and leads to a higher risk of accumulation of toxic substances, in particular heavy metals, in its seeds and sunflower processing products. The content of toxic substances in the soil during sunflower cultivation was investigated. The authors of the research compared the content of heavy metals of lead, cadmium, copper, and zinc in sunflower seeds and meal with their content in the soil. The obtained indicators were compared with the maximum permissible concentrations. The accumulation coefficients of heavy metals of lead, cadmium, copper and zinc by sunflower seeds were calculated. The amounts of heavy metal transfer from the soil to sunflower seeds and sunflower meal were calculated. Among the soil chemical toxicants that can be potentially accumulated in sunflower seeds and sunflower meal, the most dangerous are lead, copper, zinc, cadmium, cesium, and cobalt. At the same time, the amount of mercury, molybdenum, boron and iron in the studied soil does not pose a danger. At the actual level of soil contamination with mobile forms of lead, cadmium, copper and zinc within 0.13–0.26 MPC, their content in sunflower seeds was 0.11–0.17 MPC. In sunflower meal, the content of studied heavy metals more increased as compared to sunflower seeds, particulalry copper – 2.9 times, lead – 1.49 times, cadmium – 1.45 times, zinc – 1.43 times. However, the actual share of such heavy metals was 0.03–0.09 MPC in relation to the maximum permissible concentration. The highest coefficient of accumulation of the heavy metals by sunflower seeds from the soil was marked for zinc – 1.81 and copper – 1.71, while for lead and cadmium, it was 0.06 and 0.12, respectively.